Neanderthals’ recolonizations of marginal areas: An overview from Eastern Germany - Andrea Picin (Quaternary Science Advances)
The Middle Paleolithic in Eastern Germany presents a unique context for understanding Neanderthal populations' dynamics within environmental shifts. The cyclical ice-sheet growth and advancements during the late Middle and Late Pleistocene caused occupational gaps in North-western and Central Europe and recurring episodes of recolonization from the southern regions. From cold tundra and steppe landscapes to forested habitats during climatic amelioration, these environmental changes significantly influenced Neanderthal settlement patterns and adaptive strategies. In this study, the lithic assemblages from some Middle Paleolithic sites stretched between Saxony and Saxony-Anhalt are analyzed. Despite migrations occurring over millennia, our study reveals that the unidirectional reduction scheme was continuously applied to different knapping methods remaining a common technological substrate during the whole Middle Paleolithic. The introduction of asymmetric bifacial tools during MIS 5c/MIS 5a did not alter predominant flake production methods. Contrariwise to support a techno-cultural stasis lasted several millennia, this study reveals that this technical continuity could be related to the changes in raw material size occurred during the Middle Pleistocene. Large erratic flint nodules during the Elsterian glaciation promoted loss-making behaviors, while the transport of smaller nodules during the Drenthe glaciation encouraged more intensive exploitation of pebbles during the Late Middle Paleolithic. By shedding light on Neanderthal lifeways, technological adaptations, and settlement patterns in Eastern Germany, this research contributes to a nuanced understanding of their behavior amidst evolving environmental conditions.